(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Today, artificial intelligence is a rapidly developing technology. It is applied in many aspects of our daily lives, such as intelligent search engines, self-driving cars, and intelligent agents. As technology advances, intelligent agents become more popular. Smartphones and smart speakers like Amazon Echo have made them ubiquitous. Some of the most well-known examples of current conversational agents are Siri, Cortana, Alexa, and Google Assistant. The advent of AI-driven chatbots is revolutionizing customer service by delivering instant responses, efficiently addressing queries, and slashing wait times. Exactly, chatbots are crafted to mimic human behavior and effectively take on the role of humans in a chat environment. Many companies, particularly in e-commerce, leverage chatbots across various platforms as a means to connect with their customers, offering an efficient and automated way to engage in conversations and provide assistance. Indeed, chatbots possess the ability to continuously learn. This paper serves as a foundation for comprehending the subsequent evolution of chatbots. Firstly, we will delve into artificial intelligence, providing an overview that encompasses its historical development, along with comprehensive definitions and explanations of its various manifestations. Following that, we will define the term “chatbot” and provide an overview of its three primary categories: template-based models, retrieval-based models, and generative-based models. Lastly, the study will explore the impact of chatbots on the online marketplace’s customer experience. We will investigate the factors that influence the platform’s customer experience, the potential enhancements that chatbots can offer, and their effectiveness in addressing customer inquiries and grievances.